Four new nematode species (Araeolaimida: Comesomatidae, Diplopeltidae) from the New Zealand continental slope - Leduc, Daniel (Zootaxa, 2017)
Four new nematode species of the order Araeolaimida are described from the continental slope of New Zealand: Sabatieria megadena sp. n., Pararaeolaimus tetradenus sp. n., Southerniella parasimplex sp. n., and Diplopeltula cuspidiboja sp. n. The present study provides the first record of the genus Pararaeolaimus in the New Zealand Exclusive Economic Zone. Pararaeolaimus megaloamphidus Timm, 1961, Diplopeltula mollis Bussau, 1993 and Diplopeltula peruensis Bussau, 1993 are considered species inquirendae due to the incomplete nature of the original descriptions. Southerniella amblynema Bussau, 1993, Southerniella lympha Bussau, 1993, and Southerniella nojii Jensen, 1991 are transferred to the genus Intasia Tchesunov & Miljutina, 2008 due to the presence of a single anterior outsretched ovary. A key to valid Southerniella species is provided.